Analisis Penerapan Metode Activity Based Costing dalam Penentuan Harga Pokok Produksi pada UMKM Nurul Aini Mojokerto Tahun 2024 - Rahmat Hidayat; Hartono Hartono; Toto Dwihandoko (Jurnal Riset Ekonomi dan Akuntansi, 2024)
The purpose of this study was to determine and analyze the calculation of the cost of production at Nurul Aini UMKM in Mojokerto using traditional accounting and determining the cost of production based on the activity-based costing (ABC) method. This study uses a quantitative descriptive approach. Data were collected through documentation and interviews. The analysis used is quantitative descriptive analysis, which is an analysis based on decisions. The results of the study are as follows: 1. By using a traditional approach to calculate the cost of production at Nurul Aini UMKM, it was found that the raw materials used to produce motorcycle seats were 37,253,166,000, labor costs were 2,350,570,000, and factory overhead costs were 339,960,000. Thus, the cost of production of Nurul Aini UMKM in 2023 is IDR 39,943,696,000. 2) The activity-based costing system is used to calculate the COGS of Nurul Aini UMKM. To begin, the costs of activity resources must be examined. It begins by identifying and dividing activities into four levels of activity: unit level, batch-related costs, product enhancement costs, and facility enhancement costs. Next, product costs must be examined. where the cost drivers used by each product are used to limit factory overhead costs.